RELATIONSHIP BETWEEN THE DEMOGRAPHIC CHARACTERISTICS AND THE EFFECTIVENESS OF E-BANKING TRAINING COURSES BASED ON KIRKPATRICK MODEL FOR EMPLOYEES OF MASKAN BANK BRANCHES IN TEHRAN, IRAN - Rezayat, Bahman; Nasiri, Roxana; Shariatmadari, Mahdi (PEOPLE: International Journal of Social Sciences, 2018)
This study was carried out aimed to measure the Relationship between demographic characteristics and the effectiveness of e-banking training courses for employees of Maskan Bank Branches in Tehran province. The research method in terms of objective is considered as an applied research and information collection method is descriptive-survey. The statistical population of this research includes all employees of Maskan Bank Branches in Tehran Province who have participated in e-banking courses and have a population of about 1100 people. The statistical population of this study includes all employees of Maskan Bank Branches in Tehran Province who have participated in e-banking training courses and have a population of about 1100 people. 285 people were selected using Morgan table and by simple random sampling method. The tool measurement used was questionnaire based on the Kirkpatrick model in four levels of reaction, learning, behavior and results, which its reliability was calculated using Cronbach’s alpha coefficient, 0.89 and it was confirmed. Descriptive and inferential statistical methods (one-way t-test, one-way ANOVA and Pearson correlation coefficient) were used in order to analyze the obtained data. According to the results of t-test, e-banking training courses were effective for employees of Maskan Bank Branches in Tehran province. Also, the analysis of demographic findings based on the results of the one-way between-subjects ANOVA showed that employees’ attitudes at different positions, work experience or education level were not significantly different towards the factors affecting the effectiveness of e-banking training courses and none of them should be omitted from e-banking courses.